PENGAWASAN LEGISLASI DAERAH OLEH DPD: TANTANGAN ERA DISRUPSI HUKUM - Indra L Nainggolan (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Control authority of the DPD in Article 22D of the 1945 Constitution of the Republic of Indonesia has expanded to include regional law products, both draft regional regulations, and regional regulations. Control referred to in Article 249 paragraph 1 letter j of Law No. 2 of 2018 is not a legislative review or cancellation of regional regulations. Monitoring and evaluation of draft regional regulations and regional regulations by the DPD is a broad interpretation of the legislative function, control function, and representation function. Monitoring and evaluation of regional regulations and regional regulations will ultimately carry out the function of regional representation. Regions in the context of a unitary state have representatives at the center to fight for their aspirations which are outlined in the form of national policies. Such a position makes the DPD have a major role in carrying out its representation as external control of draft regional regulations and regional regulations. The era of legal disruption demands a more responsive and innovative role for the DPD in carrying out various regional aspirations. The control practices carried out should not use the old method which is actually considered to hinder the implementation of the authority it has. The research method used is normative juridical by using library research.Keywords: Control; Draft Regional Regulations; Regional Regulations; Legal Disruption AbstrakKewenangan pengawasan DPD pada pasal 22D UUD NRI 1945 berkembang luas hingga pada produk hukum daerah baik ranperda dan perda. Pengawasan yang dimaksud pada pasal 249 ayat 1 huruf j UU No.2 Tahun 2018 bukanlah legislative review atau pembatalan peraturan daerah. Pemantauan dan evaluasi atas rancangan peraturan daerah dan peraturan daerah oleh DPD merupakan intrepretasi luas dari fungsi legislasi, fungsi pengawasan, dan fungsi representasi. Pemantauan dan evaluasi ranperda dan perda pada akhirnya melaksanakan fungsi keterwakilan daerah. Daerah dalam konteks negara kesatuan memiliki perwakilan di pusat guna memperjuangkan aspirasinya yang dituangkan dalam bentuk kebijakan nasional. Posisi demikian membuat DPD memiliki peran besar dalam menjalankan keterwakilannya sebagai pengawas eksternal terhadap ranperda dan perda. Era disrupsi hukum menuntut peran DPD lebih responsif dan inovatif  dalam menjalankan aspirasi daerah yang beragam. Praktik pengawasan yang dilakukan jangan sampai menggunakan cara lama yang justru dianggap menghambat pelaksanaan kewenangan yang dimilikinya. Metode penelitian yang digunakan yuridis normatif dengan menggunakan studi kepustakaan.Keyword: Pengawasan; Ranperda; Perda; Disrupsi Hukum